CCN4/WISP-1 positively regulates chondrogenesis by controlling TGF-β3 function - Yoshioka, Yuya; Ono, Mitsuaki; Maeda, Azusa; Kilts, Tina M.; Hara, Emilio Satoshi; Khattab, Hany; Ueda, Junji; Aoyama, Eriko; Oohashi, Toshitaka; Takigawa, Masaharu; Young, Marian F.; Kuboki, Takuo (Bone (New York, N.Y.), 2016)
The CCN family of proteins plays important roles in development and homeostasis of bone and cartilage. To understand the role of CCN4 in chondrogenesis, human bone marrow stromal cells (hBMSCs) were transduced with CCN4 adenovirus (adCCN4) or siRNA to CCN4 (siCCN4) in the presence or absence of transforming growth factor-β3 (TGF-β3). Overexpression of CCN4 enhanced TGF-β3-induced SMAD2/3 phosphorylation and chondrogenesis of hBMSCs in an in vitro assay using a micromass culture model. On the other hand, knockdown of CCN4 inhibited the TGF-β3-induced SMAD2/3 phosphorylation and synthesis of cartilage matrix in micromass cultures of hBMSCs. Immunoprecipitation–western blot analysis revealed that CCN4 bound to TGF-β3 and regulated the ability of TGF-β3 to bind to hBMSCs. In vivo analysis confirmed there was a significant decrease in the gene expression levels of chondrocyte markers in cartilage samples from Ccn4-knock out (KO) mice, compared to those from wild type (WT) control. In order to investigate the regenerative properties of the articular cartilage in Ccn4-KO mice, articular cartilage defects were surgically performed in the knee joints of young mice, and the results showed that the cartilage was partially repaired in WT mice, but not in Ccn4-KO mice. In conclusion, these results show, for the first time, that CCN4 has a positive influence on chondrogenic differentiation by modulating the effects of TGF-β3. •Gene expression levels of CCN4 are up-regulated during chondrogenesis.•CCN4 is a positive regulator of TGF-β3-induced chondrogenesis of hBMSCs.•CCN4 enhances binding affinity of TGF-β3 to hBMSCs.•Healing of articular cartilage in Ccn4 deficient mice is delayed.